IT leadership manual : roadmap to becoming a trusted business partner - Guibord, Alan R., 1947- (ITpro collection, 2012)
Savvy advice for developing the necessary skills to become a vital part of any management team Today's IT leaders are faced with an unprecedented leadership and organizational challenge. The entire landscape has changed over the past few years and it is now time for leaders and organizations to re-invent themselves to meet the new order. IT leaders need to redefine their role into one of being a trusted business advisor. IT Leadership Manual provides you with a set of specific recommendations and suggestions to assist you in your self-evaluations and to develop a personal plan for the future.